The correct answer of the question is 3{-1+√5}/ 2 or 3{-1-√5}/ 2 .
The given quadratic equation is 3 x²+ 9 x=27
To begin, we must transform the equation in the form
ax² + bx + c = 0, then apply the quadratic formula i.e.
x = {-b±√(b²- 4ac)}/ 2a .
Now,
3 x²+ 9 x=27
⇒ 3 x²+ 9 x - 27 = 0
⇒ 3(x²+ 3 x - 9 )= 0
⇒ x²+ 3 x - 9 = 0
Here, a = 1, b = 3 and c = --9
Now, applying quadratic formula
{-b±√(b²- 4ac)}/ 2a
= {-3±√(3²- 4 × 1 × -9)}/ (2 × 1)
= {-3±√(9 + 36)}/ 2
= {-3±√45}/ 2
= {-3±3√5}/ 2
= 3{-1 ±√5}/ 2
= 3{-1+√5}/ 2 or 3{-1-√5}/ 2
Therefore, the ultimate answer to the given equation is 3{-1+√5}/ 2 or 3{-1-√5}/ 2 .
Learn more about Quadratic formula here- brainly.com/question/1214333 "
#SPJ4